Approaches to the Development of Logical Thinking of Younger School children - Isroiljonova Madinabonu Shuxratjon kizi (Periodica Journal, 2023)
This article discusses the methods of organizing special developmental work on the formation of logical thinking of younger schoolchildren, contributing to the fullest manifestation of their abilities, the development of initiative, independence, creativity, and the effectiveness of the process of developing logical thinking of younger schoolchildren
Keywords: promotes the development of logical thinking; initiative; independence; creativity